Linear optical properties of zinc borotellurite glass doped with lanthanum oxide nanoparticles for optoelectronic and photonic application - Mohd Fudzi, Faznny; Mohamed Kamari, Halimah; Abd Latif, Amirah; Abd Azis, Muhammad Noorazlan (Hindawi Publishing Corporation, 2017)
Enhancing the optical properties of glasses for the sake of optical application in various fields is an ongoing challenge in materials science and technology. Thus, the optical properties of zinc borotellurite glass doped with lanthanum oxide nanoparticles (La2O3 NPs) with the chemical composition of {[(TeO2)0.7(B2O3)0.3]0.7(ZnO)0.3}1−x (La2O3 NPs)x, where x = 0.01, 0.02, 0.03, 0.04, and 0.05 molar fraction, have been investigated. Characterization techniques such as x-ray diffraction, Fourier Transform Infrared Spectroscopy, and Ultraviolet-Visible Spectroscopy are employed to yield the structural properties and optical parameter of the glass. The amorphous nature of the fabricated glasses is confirmed with the presence of a broad hump via XRD diffraction pattern. The decreasing amount of high polarizable nonbridging oxygen as the concentration of La2O3 NPs increases has contributed to the increasing trend of energy band gap in the range of 2.70 to 3.52 eV and decreasing value of refractive index between 2.34 and 2.48. The fabricated glasses that have a higher refractive index than the widely used fiber material, pure silica glass, indicate that zinc borotellurite glass doped with lanthanum nanoparticles is a promising material to be applied as optical fibers.